Nrf2 Deficiency Exacerbates Obesity-Induced Oxidative Stress, Neurovascular Dysfunction, Blood–Brain Barrier Disruption, Neuroinflammation, Amyloidogenic Gene Expression, and Cognitive Decline in Mice, Mimicking the Aging Phenotype. (7th October 2017) - Tarantini, Stefano; Valcarcel-Ares, M Noa; Yabluchanskiy, Andriy; Tucsek, Zsuzsanna; Hertelendy, Peter; Kiss, Tamas; Gautam, Tripti; Zhang, Xin A; Sonntag, William E; de Cabo, Rafael; Farkas, Eszter; Elliott, Michael H; et al.
Abstract: Obesity has deleterious effects on cognitive function in the elderly adults. In mice, aging exacerbates obesity-induced oxidative stress, microvascular dysfunction, blood–brain barrier (BBB) disruption, and neuroinflammation, which compromise cognitive health. However, the specific mechanisms through which aging and obesity interact to remain elusive. Previously, we have shown that Nrf2 signaling plays a critical role in microvascular resilience to obesity and that aging is associated with progressive Nrf2 dysfunction, promoting microvascular impairment. To test the hypothesis that Nrf2 deficiency exacerbates cerebromicrovascular dysfunction induced by obesity Nrf2 +/+ and Nrf2 -/-, mice were fed an adipogenic high-fat diet (HFD). Nrf2 deficiency significantly exacerbated HFD-induced oxidative stress and cellular senescence, impairment of neurovascular coupling responses, BBB disruption, and microglia activation, mimicking the aging phenotype. Obesity in Nrf2 -/- mice elicited complex alterations in the amyloidogenic gene expression profile, including upregulation of amyloid precursor protein. Nrf2 deficiency and obesity additively reduced long-term potentiation in the CA1 area of the hippocampus. Collectively, Nrf2 dysfunction exacerbates the deleterious effects of obesity, compromising cerebromicrovascular and brain health by impairing neurovascular coupling mechanisms, BBB integrity and synaptic function and promoting neuroinflammation. These results support a possible role for age-related Nrf2 dysfunction in the pathogenesis of vascular cognitive impairment and Alzheimer's disease.